Características clínicas y grado de discapacidad en pacientes con dolor lumbar crónico en consultorio de neurocirugía del Hospital Regional de Loreto abril - mayo 2025 - Morales Guzmán, César Alexander (2025)
Chronic low back pain is one of the leading causes of medical consultation and disability worldwide. The objective of this study was to determine the clinical, epidemiological characteristics, and degree of disability in patients with chronic low back pain treated at the outpatient neurosurgery clinic of the Regional Hospital of Loreto during April–May 2025. A qualitative, observational, cross sectional, and analytical study was conducted in 113 patients. The most frequent age group was 45–59 years (32.7%), followed by 30–44 years (31.9%), with a predominance of females (54.9%). The most common occupations were housewives (31.0%) and police officers (22.1%). Radicular pain predominated (85.8%) along with mechanical etiology (94.7%). The most frequent comorbidities were metabolic-endocrine diseases (19.5%) and cardiovascular diseases (16.8%). Overweight was the most common nutritional condition (46.9%), followed by normal weight (31.0%) and grade 1 obesity (19.5%). Most patients presented severe pain (76.1%), while the remainder had moderate pain (23.9%), with no cases of absence of pain or mild pain. Intense functional limitation was the most frequent outcome (43.4%), followed by moderate limitation (24.8%) and disability (22.1%). In the association analysis, male sex was identified as being related to a higher probability of presenting severe functional limitation (p = 0.047). No statistically significant associations were found for the other variables evaluated.